อิทธิพลระหว่างประเทศที่มีต่อกฎหมายอาญาไทย : ศึกษากรณีองค์กรอาชญากรรม - ปาณิศา พัวเวส (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
Problems concerning organized crime are among crucial problems facing Thailand and the world community. Nations sought various legal measures to solve and to eradicate organized crime. Thailand, in particular, adopted penal provisions pertaining to the offenses of Criminal Association and Illegal Secret Society in order to maintain public peace and prevent law infringement occurred by an organization whose proceedings are secret. These early twentieth century provisions could not possibly deal with modern and complex operation of organized crime of the present day. Thailand, therefore, adopted modern legal measures which hopefully will do away with organized crime. In the past decade, new measures have been taken from both international agreements and international laws. Notwithstanding the adoption of modern measures, the problems still persist. This thesis finds that the revised laws lack of uniformity thereby they are inefficient and difficult to enforce. At present, the limitation on accessing to the true body of criminal organization has not been improved. This research recommends the improvement of the penal code provisions on secret society and criminal association offences. Revision of the provisions is required to include internationally recognized principles and necessary measures. Hence these penal provisions shall be the main legal body to deal with organized crime. In addition, the state could enforce other acts as auxiliary measures. Ultimately, the more effective prosecution of organized crime shall be achieved.